2013
DOI: 10.1080/02640414.2013.764466
|View full text |Cite
|
Sign up to set email alerts
|

The effect of caffeine ingestion on skill maintenance and fatigue in epee fencers

Abstract: The ergogenic effect of caffeine on sports performance focuses predominantly on endurance sports (Doherty & Smith, 2004 ) with little research on intermittent high intensity sports. This study aimed to explore the effect of caffeine ingestion on skill maintenance following fencing simulated exercise. Eleven competitive fencers participated (four female; seven male; age 33 ± 6.5 years). Following a maximal test to exhaustion, fencers completed two trials assessing accuracy and reaction times (Stroop test) befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 34 publications
3
21
1
Order By: Relevance
“…Supplementation as low as 2 mg • kg −1 caffeine had a significant effect on Stroop test performance in males following exhaustive exercise but there was no main effect on either simple or CRT (Hogervorst et al, 1999). In contrast, 3 mg • kg −1 caffeine had no effect on Stroop test performance postexhaustive exercise in a mixed-gender population of epee fencers (Bottoms, Greenhalgh, & Gregory, 2013). In team-sport players, 6 mg • kg −1 caffeine had no effect on CRT following a multiple sprints protocol (Carr, Dawson, Schneiker, Goodman, & Lay, 2008) yet 5 mg • kg −1 caffeine taken in coffee decreased CRT (reaction time only) in soccer players performing cycling exercise to exhaustion (Kruk et al, 2001).…”
Section: Discussioncontrasting
confidence: 53%
“…Supplementation as low as 2 mg • kg −1 caffeine had a significant effect on Stroop test performance in males following exhaustive exercise but there was no main effect on either simple or CRT (Hogervorst et al, 1999). In contrast, 3 mg • kg −1 caffeine had no effect on Stroop test performance postexhaustive exercise in a mixed-gender population of epee fencers (Bottoms, Greenhalgh, & Gregory, 2013). In team-sport players, 6 mg • kg −1 caffeine had no effect on CRT following a multiple sprints protocol (Carr, Dawson, Schneiker, Goodman, & Lay, 2008) yet 5 mg • kg −1 caffeine taken in coffee decreased CRT (reaction time only) in soccer players performing cycling exercise to exhaustion (Kruk et al, 2001).…”
Section: Discussioncontrasting
confidence: 53%
“…In particular, several studies assessing inhibitory control using the Stroop colour-word test (also regarded as a frontal lobe task) have shown inconsistent findings with regards to caffeine's effects. Edwards et al (1996) found no effect of two different caffeine doses (125mg and 250mg) on Stroop performance (computerized or traditional card version), Bottoms et al (2013) found no change in time to complete the Stroop task after caffeine consumptions. Whereas Kenemans et al (1999) showed caffeine to reduce interference during this task in one of their studies but not the other.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, Ali et al [ 21 ] observed that a caffeine dose of 6 mg/kg effectively decreased RT in the Stroop task among female football players. However, another study found that caffeine did not have an effect on the Stroop performance after exercise [ 22 ]. The differences in these results may be related to the sensitivity of participants to various exercise types, cognitive tests, or caffeine doses.…”
Section: Introductionmentioning
confidence: 99%